Constraint-induced Movement Therapy in Patients with Upper Limb Peripheral Nerve Injury - Hamid Reza Rostami; Batol Mandani; Meimanat Akbari (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Background and Objective: Upper limb peripheral nerve injuries due to secondary changes in cortical maps cause to long lasting or sometimes permanent sensory-motor impairments. Aim of this study was to determine feasibility and efficacy of constraint-induced movement therapy (CIMT) on upper limb function in patients with peripheral nerve injuries. Subjects and Methods: In a clinical trial, a convenience sample of 7 patients with median and ulnar nerve injuries (5 men, 2 women; mean age: 28 years) were measured. Following screening and signing informed consent, patients received an intensive practice program for 1.5 hours daily, 5 days per week, during 4-week period while their healthy hand was immobilized using a volar wrist and forearm splint during waking hours. Outcome measures including Semmes Weinstein Monofilaments (SWM), Nine-hole Peg Test (9-HPT), and Motor Activity Log (MAL) questionnaire were administered pre, and post, and 4 weeks after the treatment period.Results: Data analysis did not show any changes in touch perception at tip of the fingers in SWM at post-test session; however, affected hand motor performance in 9-HPT and affected hand’s amount of use in activities of daily living according to MAL were significantly improved at the post-test session (P< 0.01) and this improvement was maintained at the follow up (P> 0.05). Conclusion: CIMT can be considered as an appropriate technique in rehabilitation program for patients with peripheral nerve injuries.